Peran Sarikat Pekerja dan Organisasi Profesi dalam Pengembangan Sumber Daya Manusia - Kurniawati, Eti (BISMA : Business and Management Journal, 2024)
Workers associations and professional organizations have a strategic role in the development of human resources (HR). This study uses a literature study approach to identify the definitions, basic principles, and contributions of worker associations and professional organizations to the improvement of human resource quality. The findings show that these two entities are oriented towards the protection of rights, competency development, and improvement of members' welfare. With the principle of solidarity and collectivity, the workers' union focuses on the protection of the workforce through policy advocacy, while professional organizations play a role in the development of professional competencies and standardization. Both complement each other in forming competent and prosperous human resources, as well as strengthening the competitiveness of individuals and institutions.